تجنيد الفرق المتحركة للشرطة الريفية ضمن الجيش الفرنسي في الثورة 1954-1962 - البار، صباح (المركز الجامعي بلحاج بوشعيب عين تموشنت, 2022)
تهدف هذه الورقة البحثية إلى إبراز كيفية تشكيل الشرطة الريفية المتنقلة للأمن ضمن الجيش الفرنسي والأدوار التي قامت بها لمساندة القوات الفرنسية من بداية الثورة الجزائرية إلى غاية الاستقلال، وتسليط الضوء على الأساليب التي استخدمتها الإدارة الفرنسية في تجنيدهم، وأهداف فرنسا من وراء تجنيد الجزائريين ضمن هذه الفرق، والمهام التي أوكلت لهم. اعتمدت في هذه الدراسة على منهجين: المنهج التاريخي الوصفي في ترتيب الأحداث التاريخية كرونولوجيا، وسرد الوقائع والأحداث التاريخية، والمنهج التحليلي في وضع الأحداث في إطارها الزماني والمكاني وتحليل الأسباب والوصول إلى النتائج. وقد تم التوصل إلى أن فرنسا قامت بتشكيل فرق الشرطة الريفية المتنقلة للأمن متكونة من رجال مدنيين مجندين من طرف الإدارة المدنية مرتبطين بتعاقد، أوكلت لهم عدة أعمال إدارية وعسكرية واستخباراتية من أجل القضاء على الثورة. وفي ضوء هذه النتائج لا يسعنا إلا أن نوصي الباحثين التعمق والبحث في الموضوع وذلك لنقص الدراسات والبحوث فيه. This research paper aims to highlight how the mobile rural police were formed within the French army and the roles they player to support the French forces from the beginning of the Algerian revolution until independence, and to shed light on the methods used by the French administration to recruit them, and France’s goals behind recruiting Algerians within these teams. And the tasks assigned to them. In this study, I relied on two approaches: the descriptive historical approach in arranging historical events chronologically, narrating historical facts and events, and the analytical approach in placing events in their temporal and spatial framework, analyzing the causes and arriving at the results. It has been concluded that France has formed mobile rural police teams for security, consisting of civilian men recruited by the Civil Administration, bound by contract, entrusting them with several administrative, military and intelligence tasks in order to put an end to the revolution. In light of these results, we can only recommend researchers to delve deeper and research the subject, due to the lack of studies and research in it.
Keywords: التنظيمات العسكرية -- المناطق الريفية -- السلطات الاستعمارية -- القوات الفرنسية -- الكتابات التاريخية